Protective Effect of Baicalin against Clostridioides difficile Infection in Mice - Abraham Joseph Pellissery; Poonam Gopika Vinayamohan; Deepa Ashwarya Kuttappan; Neha Mishra; Breno de Oliveira Fragomeni; Kendra Maas; Shankumar Mooyottu; Kumar Venkitanarayanan (Antibiotics, 2021)
This study investigated the prophylactic and therapeutic efficacies of baicalin (BC), a plant-derived flavone glycoside, in reducing the severity of Clostridioides difficile infection (CDI) in a mouse model. In the prophylactic trial, C57BL/6 mice were provided with BC (0, 11, and 22 mg/L in drinking water) from 12 days before C. difficile challenge through the end of the experiment, whereas BC administration started day 1 post challenge in the therapeutic trial. Both challenge and control groups were infected with 106 CFU/mL of hypervirulent C. difficile BAA 1803 spores or sterile PBS, and the clinical and diarrheal scores were recorded for 10 days post challenge. On day 2 post challenge, fecal and tissue samples were collected from mice prophylactically administered with BC for microbiome and histopathologic analysis. Both prophylactic and therapeutic supplementation of BC significantly reduced the severity of colonic lesions and improved CDI clinical progression and outcome compared with control (p < 0.05). Microbiome analysis revealed a significant increase in Gammaproteobacteria and reduction in the abundance of protective microbiota (Firmicutes) in antibiotic-treated and C. difficile-infected mice compared with controls (p < 0.05). However, baicalin supplementation favorably altered the microbiome composition, as revealed by an increased abundance in beneficial bacteria, especially Lachnospiraceae and Akkermansia. Our results warrant follow-up investigations on the use of BC as an adjunct to antibiotic therapy to control gut dysbiosis and reduce C. difficile infection in humans.